The lived experience of Anishinaabe people with cancer: a focus on Indigenous healing, Western medicine and Minobimaadiziwin - Peltier, Cindy M. (Laurentian University of Sudbury, 2015)
Cancer is a leading cause of death in Anishinaabe people and the incidence is increasing. Despite reported successes of integrating Indigenous healing and Western medicine in the treatment of addictions, domestic violence, mental health, palliative care and chronic illness, there is a paucity of such information for cancer. A number of studies highlighted the need for awareness for policy makers and physicians of the contribution of Indigenous healing to cancer care, as well as the need for cultural safety. This Indigenous inquiry examined potential benefits and challenges of including Indigenous healing in cancer care. Using a participatory approach, I investigated how the cancer experience was affected when Anishinaabe people included both Indigenous and Western medicine in treatment and when they did not. This inquiry also examined how Indigenous healing assisted in achieving Minobimaadiziwin, an Anishinaabe understanding of health. Interviews were conducted with thirteen adults diagnosed with cancer from five Manitoulin First Nation communities. Seventeen key informant interviews were conducted with those working from Indigenous and Western health perspectives. A conversational method was employed in this Indigenous research as it honoured the oral tradition of the Anishinaabe and was concerned with co-creating knowledge in a relational context. Understanding stories involved Indigenous knowledge and Western theory, framed as two-eyed seeing. Participants recognized that Minobimaadiziwin could not be realized with Western medicine alone. With the inclusion of IH/TM and recognition of the spiritual component of life, a person can approach Minobimaadiziwin despite the obstacle of cancer along their path. This is best iv facilitated by braiding the two types of healing. Dissemination of results took two forms: a collective, teaching story for the Anishinaabe people concerning cancer and Minobimaadiziwin and publications concerning potential benefits of and challenges with pluralistic medicine for Anishinaabe ...